2018
DOI: 10.1017/s1368980018002148
|View full text |Cite
|
Sign up to set email alerts
|

Use of added sugars in packaged foods sold in Brazil

Abstract: Most of the packaged foods sold in Brazil contain added sugars, which may hamper adherence to the recommendation of limiting added sugars intake. The data may be useful for monitoring tendencies in the use of added sugars in packaged foods and as supplementary information to support the improvement of food label regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
10
0
3
Order By: Relevance
“…Notwithstanding the higher amounts of carbohydrates in children’s products from groups 4, 5 and 7, the Brazilian regulation for nutrition labeling states that disclosing data for total sugars content is not mandatory [30]. Besides that, previous analysis performed on this database aimed at assessing the presence and types of added sugars in packaged foods identified that most of these contain added sugars, which may hamper adherence to the recommendation of limiting added sugar intake [31].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the higher amounts of carbohydrates in children’s products from groups 4, 5 and 7, the Brazilian regulation for nutrition labeling states that disclosing data for total sugars content is not mandatory [30]. Besides that, previous analysis performed on this database aimed at assessing the presence and types of added sugars in packaged foods identified that most of these contain added sugars, which may hamper adherence to the recommendation of limiting added sugar intake [31].…”
Section: Discussionmentioning
confidence: 99%
“…Para el nutriente critico azúcar, de los alimentos sólidos procesados solo la subcategoría Snack dulce tendría el etiquetado frontal en la primera etapa de implementación, mientras que casi todas las subcategorías de los sólidos ultraprocesados contarían con dicha advertencia a excepción de la subcategoría Galletas saladas y Sopas/fideos instantáneos; en los alimentos líquidos procesados y ultraprocesados todas las subcategorías iniciarían con el etiquetado frontal en alguna proporción del total de alimentos evaluados. Debemos resaltar que las subcategorías Leche procesada y Yogurt natural y Bebidas lácteas aromatizadas y azucaradas siendo alimentos recomendados para población infantil presentarían una elevada proporción de etiquetado frontal en sus productos, la cantidad de azúcar encontrada en nuestro estudio es similar a los resultados encontrados en Brasil 28 , Australia, Inglaterra y Sudáfrica 29 , próximas investigaciones deben evaluar los alimentos dirigidos para lactantes y su contenido de azúcar en el Perú, teniendo evidencia que promueven el consumo de azúcar desde edades tempranas y a largo plazo contribuyen con la prevalecía de enfermedades crónicas no transmisibles en la población 30 , requiere que se incluya en la normatividad peruana el etiquetado frontal en los alimentos para lactantes.…”
Section: Característicaunclassified
“…This means that consumers can only determine whether a product contains free sugar by identifying free sugar ingredients (FSI) from the ingredient list. However, given that many different types of FSI are found in the food supply [20,21], this may prove challenging for some consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous types of FSI are used by manufacturers including sucrose, high-fructose corn syrup (HFCS), honey, and glucose [21,22]. Each sugar is metabolized differently after consumption and therefore may lead to different health effects [23].…”
Section: Introductionmentioning
confidence: 99%